Combining morphological and molecular information to infer phylogenetic relationships of lamniform sharks - Cona, Sebastián; Cornejo, Claudio; Hernández, Sebastián; Ibáñez, Christian M. (Revista de Biología Marina y Oceanografía, 2022)
Sharks of the order Lamniformes are restricted to 15 extant species grouped into 10 genera and 8 families. These species are characterized by two spine-less dorsal fins and a ring-shaped intestinal valve. Their phylogenetic relationships are not congruent among different methods and approaches, such as the use of morphological or molecular data. The present study evaluates the phylogenetic relationships of species of the order Lamniformes by means of phylogenetic reconstructions through Bayesian inference based on morphological and molecular data and using both datasets combined. The consensus tree of the morphological Bayesian reconstruction shows that Lamnidae and Alopiidae are monophyletic, while Odontaspididae is polyphyletic. Eight synapomorphies are detected in Alopiidae, six in Lamnidae, and one for Odontaspididae. In the Bayesian molecular reconstruction consensus tree, Lamnidae and Odontaspididae are monophyletic, and Alopiidae is polyphyletic. In the consensus tree of the Bayesian reconstruction of combined data, Lamnidae, Alopiidae and, Odontaspididae are monophyletic. The results obtained suggest that posterior probabilities increase when using combined characters in a Bayesian phylogenetic analysis, which is greatly advantageous for systematics of the order Lamniformes. Due to the presence of non-monophyletic groups, monotypic families, and the strong support for the division of lamniforms into two clades, a crucial review for the classification of species is needed.